Thinking outside the (Witness) Box: Integrating Experts into Juries to Minimise the Effect of Rape Myths in Sexual Violence Cases - Retter, Amelia Erin (Victoria University of Wellington Law Review, 2018)
The criminal justice system's response to sexual violence has been increasingly recognised as an area needing attention. In particular, rape myths have a significant impact on whether a victim is believed or not, and this extends to the jury. Due to the potential effect of misconceptions about sexual violence on the jury's decision-making process, alternatives and additional tools have been suggested to minimise this impact. This article looks at options for moving forward such as increasing education and guidance for the jury, as well as changing the fact-finder, but ultimately advocates a new approach of integrating experts with knowledge about sexual violence and its realities into the jury itself. This would allow for responses tailored to each case to create an educative mechanism while maintaining lay participation, and have decisions that are based on accurate understandings of sexual violence.